(untitled) (Diametros, 2025)
I argue that strong intuitions about how the state ought to allocate healthcare are incompatible with quite influential autonomy-centric and neutral strains of liberal political theory. Specifically, I maintain that it is uncontroversial that we should routinely distribute medical treatments in public hospitals in ways that have little to no bearing on patients’ ability to pursue a wide array of ends and further that we cannot easily avoid making judgments of which ways of life are good (or bad) when making such distributions. These intuitions tell against the principles that the state in general should aim merely to protect individuals’ rights to choose their own ways of life and should not take sides on which lives are good (or bad) when adopting policy or law. I show that this tension, which has not been addressed in the literature, manifests in at least three types of healthcare decisions, viz., which types of treatments should be offered to patients, how to prioritize among types of treatments, and who should receive a certain type of treatment. I do not prescribe how to resolve the tension, that is, whether to reject autonomy-centric and neutral forms of liberalism or revise judgments about how public medical facilities should allocate healthcare, but instead I establish the point that one must choose between them.